2010
DOI: 10.1124/mol.109.061481
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate (S1P) Regulates Vascular Contraction via S1P3 Receptor: Investigation Based on a New S1P3 Receptor Antagonist

Abstract: Sphingosine 1-phosphate (S1P) induces diverse biological responses in various tissues by activating specific G proteincoupled receptors (S1P 1 -S1P 5 receptors). The biological signaling regulated by S1P 3 receptor has not been fully elucidated because of the lack of an S1P 3 receptor-specific antagonist or agonist. We developed a novel S1P 3 receptor antagonist, 1-(4-chlorophenylhydrazono)-1-(4-chlorophenylamino)-3,3-dimethyl-2-butanone (TY-52156), and show here that the S1P-induced decrease in coronary flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 42 publications
3
122
0
Order By: Relevance
“…It is possible that receptors other than S1P1 may play a role in these effects. Murakami et al 46 showed that S1P influences VSMC contraction through S1P3 receptors, and Takashima et al 47 demonstrated that VSMC migration involves S1P2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that receptors other than S1P1 may play a role in these effects. Murakami et al 46 showed that S1P influences VSMC contraction through S1P3 receptors, and Takashima et al 47 demonstrated that VSMC migration involves S1P2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Although several types of Notch inhibitors are quite effective in preclinical models 21,48,49 , none of the clinical trials conducted so far has examined effectiveness 50 . This prompts us to encourage efforts to explore alternative/ additional approaches for targeting Notch.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of S1P were blocked by the S1PR3 antagonist TY52156 (ref. 21). Another antagonist CAY10444, which is structurally different from TY52156, also inhibited the S1P effect.…”
mentioning
confidence: 99%
“…S1P 1 signaling reporter mice demonstrate receptor activation in endothelium under basal conditions, with enhanced S1P activation, dependent on plasma S1P, when systemic inflammation is induced (42). S1P 2 and S1P 3 are also expressed in vascular smooth muscle cells of resistance vessels and regulate vascular tone, especially during endothelial damage when plasma S1P accesses the medial smooth muscle cells (43)(44)(45)(46)(47). Alternatively, during injury or activation of vascular smooth muscle, enhanced activation/expression of sphingosine kinases could induce local S1P production within the vessel wall to influence vascular tone.…”
Section: S1p Metabolismmentioning
confidence: 99%